Implementation of Decision Support System for Seed Award Recipient Student Selection at Madrasah Ibtidaiyah Baiturrahman, Bandung, West Java - Salma Latifa Azzahra; Raisah Fajri Aula; Nadiya Herdiana Putri (International Journal Software Engineering and Computer Science (IJSECS), 2025)
The selection process for Seed Award recipients at Madrasah Ibtidaiyyah Baiturrahman Bandung encounters challenges related to subjective assessment and perceived inequity. The evaluation system applies uniform criteria across all students from grades 1 to 6 without accounting for developmental differences between grade levels. To address these issues, we designed and implemented a web-based Decision Support System utilizing the VIKOR method. We selected VIKOR for its ability to generate optimal compromise solutions in multi-criteria problems involving conflicting considerations. The DSS employs four primary criteria: Religious Practice 20%, Character 20%, Discipline 20%, and Grade Level 40%, with the latter formulated as a cost criterion to ensure fairness across educational levels. We built the system using Laravel framework and tested it with 17 teachers and 20 students as trial participants. Implementation results demonstrate substantial improvements in selection objectivity, evidenced by increased representation of lower-grade students from grades 1 to 2 as award recipients from 18% to 42%. Furthermore, 94% of teachers reported the system as more objective and user-friendly, 75% of students expressed increased motivation following system deployment, and parental complaints were eliminated previously ranging from 5 to 7 cases per semester. These findings indicate that VIKOR-based DSS successfully establishes fairer, more transparent, and accountable selection processes while enhancing stakeholder confidence in evaluation mechanisms within madrasah environments.